Positive Deviance in Nutritional Practices for Two-Year-Olds in Poor Fisherman Families in the Belawan Health Center Area, 2022 - Nasution, Ramadhani Syafitri; Mouliza, Nurul; Pratiwi, Debby (PT Inovasi Pratama Internasional, 2024)
The problem of malnutrition is still the main problem faced in human resource development. The problem of growth and development of Baduta is a serious problem because at this age the process of physical and intellectual growth and development is critical. Malnutrition problems mostly occur in poor families but are not caused by poor families who have well-nourished children. The Belawan Community Health Center working area is one of the community health centers with the highest number of cases of malnutrition in Medan City. To overcome this, a program is needed that is believed to be effective and sustainable. One of the existing programs to overcome the problem of malnutrition and malnutrition is positive deviation. This research aims to identify positive behavior in feeding (type of food, processing of food ingredients, mealtimes and method of feeding) of toddlers who are well-nourished in poor fishing families in the Belawan Community Health Center Working Area in 2022. This research method is qualitative research with a narrative approach. Researchers studied individual lives by asking one or several individuals to tell stories about their lives related to positive behavior in feeding well-nourished animals. This information is then retold by the researcher in a narrative chronology. The findings of this research indicate that addressing nutritional challenges in children can be effectively achieved by leveraging the potential and resources within the community. This is done through the identification of positive deviant behaviors, particularly those related to beneficial feeding practices. These practices encompass aspects such as the types of food provided, the methods of food preparation, the timing of meals, and the approach to food administration. Keep up the great work! The way you’re thinking about integrating community strengths is spot-on for creating sustainable solutions.